Watching over innovation studies: Profiling the gatekeepers - Santos, A. T.; Mendonça, S. (18th International Conference of the International Society for Scientometrics and Informetrics, 2021)
Academic serials (especially peer-reviewed journals) play a very critical role in the scientific ecosystem and both integrity and independence are perceived as essential for good editorial governance (Rynes, 2006). For being responsible for articles selection (Bedeian et al., 2009; Feldman, 2008), elite board membership ensures the scientific quality of publications and “occupy key roles as opinion formers, gatekeepers and arbiters of disciplinary values” (Burgess and Shaw, 2010, p.630). So far, board elites have not been subject to a scrutiny proportional to their decision power (Burgess & Shaw, 2010) and an overall lack of transparency has been reported about the general editorial process despite of being actual gatekeepers (Miner, 2003; see also Bedeian et al., 2009; Horan et al., 1993).